WIĘCEJ TEORII I WIĘCEJ PRAKTYKI? KSZTAŁCENIE INTERDYSCYPLINARNE I NIEDOGMATYCZNE W PROGRAMACH STUDIÓW PRAWNICZYCH AMERYKAŃSKICH UCZELNI - Zych, Tymoteusz (Zeszyty Prawnicze, 2016)
More Theory, more Practice? Interdisciplinary and NonDogmatic Education in American Law School Curricula Summary While American legal education is very often invoked as a model for Polish law faculties, the actual role of interdisciplinary and non- -dogmatic courses in the curricula of American law schools has not been coherently analysed yet. The American example shows that the concept of legal education has a significant impact on the development of the legal system. Interdisciplinary courses have been present in the curricula of university law schools since the beginning of American history. Currently the American Bar Association requires law schools to include non-dogmatic contents in their curricula to obtain accreditation. The widest range of non-dogmatic courses is offered by the most prestigious law schools. Leading American legal thinkers of all currents emphasise the importance of interdisciplinary and non-dogmatic subjects in the educational process. The paper concludes with a comparative analysis of the role of interdisciplinary subjects in law school curricula in Poland and in the United States.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />